The dosage effects of dexamethasone on osteogenic activity andbiocompatibility of poly(lactic-co-glycolic acid)/hydroxyapatite nanofibers - Chang Li; Bo Wang; Xinchen Liu; Ziyi Pan; Chao Liu; Huayu Ma; Xueyan Liu; Lijun Liu; Chao Jiang (Artificial Cells, Nanomedicine, and Biotechnology)
Poly(lactic-co-glycolic acid) (PLGA) based biomaterials have many advantages and potential applications in bone tissue engineering. Whereas, a significant problem which could not be ignored was that the acidic by-products generated during its degradation induced severe inflammatory reactions and negatively regulated bone regeneration. In this research, feasibility of using dexamethasone (Dex) to improve the biocompatibility of PLGA is investigated in detail. Hereby, various contents of PLGA/hydroxyapatite (PH) nanofibers loaded with Dex were synthesized by electrospinning technique. It was shown that 0.5% (wt) Dex in PH scaffolds was the minimum content which was required for anti-inflammatory effect. Admittedly, Dex to some extent had cytotoxic effect on osteoblasts and an inhibitory effect on ALP activity in this study; nevertheless, the relatively low Dex (<2% [wt]) had no inhibitory effects on osteoblasts maturation and mineralization. By this token, Dex is a good candidate for improving biocompatibility of PLGA based biomaterials. Moreover, the cytotoxic effects of Dex should be concerned. This study will provide a rationale for optimizing biocompatibility of PLGA based biomaterials by using Dex.